ACCELERATING THE EVOLUTION OF MSME BUSINESS TRANSACTIONS THROUGH ONLINE MARKETING, QRIS, AND GOOGLE MAPS - Siswanta Siswanta; Aris Tri Haryanto; Singgih Ariyuda (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2026)
Digital transformation has reshaped marketing, payment systems, and business visibility within micro, small, and medium enterprises (MSMEs). In rural areas, however, such transformation is often constrained by low digital literacy, limited devices, and a persistent reliance on conventional transactions. This community service program aimed to accelerate the evolution of MSME business transactions in Karangan Village, Karanganom District, Klaten Regency, through online marketing training, QRIS payment assistance, and Google Maps optimisation. The implementation employed a participatory approach that included preliminary observation, problem identification, socialisation, training, direct mentoring, and evaluation. The findings indicate improved understanding among MSME actors regarding digital promotion, cashless payment, and the importance of digital business visibility. Several businesses started using social media for promotion, accepting QRIS-based payments, and registering their locations on Google Maps. Key constraints included low initial technical capability, limited devices and internet access, and weak post-program sustainability mechanisms. The program confirms that collaboration among universities, village governments, and communities can function as a catalyst for MSME digitalization and local capacity building. Its main implication is the need for gradual, sustained mentoring to ensure that technology adoption progresses beyond training and becomes embedded in business behaviours and village service practices.